2011
DOI: 10.1152/japplphysiol.00807.2010
|View full text |Cite
|
Sign up to set email alerts
|

AMPKα2deficiency uncovers time dependency in the regulation of contraction-induced palmitate and glucose uptake in mouse muscle

Abstract: Abbott MJ, Bogachus LD, Turcotte LP. AMPK␣2 deficiency uncovers time dependency in the regulation of contraction-induced palmitate and glucose uptake in mouse muscle. J Appl Physiol 111: 125-134, 2011. First published May 5, 2011 doi:10.1152/japplphysiol.00807.2010.-AMP-activated protein kinase (AMPK) is a fuel sensor in skeletal muscle with multiple downstream signaling targets that may be triggered by increases in intracellular Ca 2ϩ concentration ([Ca 2ϩ ]). The purpose of this study was to determine whet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 58 publications
0
26
1
Order By: Relevance
“…We did not observe an increased phosphorylation of CaMKI or of CaMKII upon 7-min, 4-Hz stimulation (Fig. 2B), which is in contrast to findings in skeletal E227 CALCIUM SIGNALING AND CARDIAC SUBSTRATE UPTAKE muscle (1,48). Additionally, treatment with oligomycin or AICAR treatment did not increase phosphorylation of either kinase (Fig.…”
Section: Testing the Potential Ofcontrasting
confidence: 55%
See 1 more Smart Citation
“…We did not observe an increased phosphorylation of CaMKI or of CaMKII upon 7-min, 4-Hz stimulation (Fig. 2B), which is in contrast to findings in skeletal E227 CALCIUM SIGNALING AND CARDIAC SUBSTRATE UPTAKE muscle (1,48). Additionally, treatment with oligomycin or AICAR treatment did not increase phosphorylation of either kinase (Fig.…”
Section: Testing the Potential Ofcontrasting
confidence: 55%
“…Studies describing the role of Ca 2ϩ signaling in skeletal muscle substrate uptake often have used caffeine to increase [Ca 2ϩ ] i (1,48). Specifically, it has been shown that caffeine treatment induces CaMKK␤ and CaMKII phosphorylation concomitantly with increased glucose uptake.…”
mentioning
confidence: 99%
“…The ␣and ␤-subunits each exist in two isoforms (␣ 1 , ␣ 2 , ␤ 1 , and ␤ 2 ), and the ␥-subunit exists in three isoforms (␥ 1 , ␥ 2 , and ␥ 3 ). Some studies (1,28,30,33,57,69) have shown that mice overexpressing a dominant negative AMPK-␣ 2 construct in muscle or AMPK-␣ 1 and -␤ KO mice have impaired exercise-stimulated glucose uptake. A previous study (53) involving incubation with the AMP-analog 5-aminoimidazole-4-carboxamide ribonucleoside (AICAR) have shown that activation of AMPK is positively correlated with increased skeletal muscle glucose uptake.…”
Section: Amp-activated Protein Kinasementioning
confidence: 99%
“…Additionally, AMPKβ2 knockout mice had reduced maximal exercise capacity and AMPK activity during treadmill running compared to wild type mice [89], and muscle specific AMPKβ1β2 knockout mice showed decreased AMPKα1α2 activity and AMPK phosphorylation following exercise compared to wild type mice [90]. Following muscle contraction, glucose uptake rates did not increase until the last five minutes in hind limb muscles from AMPKα2 dominant negative mice, whereas glucose uptake rates increased rapidly and remained elevated throughout the contraction period in wild type mice [91]. A similar study on AMPKα2 dominant negative mice found that contraction induced glucose uptake was reduced by 50% in extensor digitorum longus muscle compared to the wild type mice, suggesting that AMPK activity has important role in exercise induced glucose uptake [92].…”
Section: Exercise and Insulin Signalingmentioning
confidence: 99%